Successful Delayed Interval Delivery in Twin Pregnancy After Early Premature Rupture of Membranes of a Leading Fetus: A Case Report - Won-Kyu Jang (Medicina)
A 36-year-old primigravida conceived dichorionic diamniotic twins via in vitro fertilization. The first twin experienced premature rupture of membranes at 18 weeks and 5 days of gestation. Despite antibiotic treatment, the first fetus suffered intrauterine fetal death and was delivered three days later at 19 weeks and 1 day. Using ritodrine, the remaining umbilical cord was repositioned, and an emergency cerclage was performed. Ritodrine was continuously administered post-surgery but discontinued at 24 weeks and 3 days due to improved uterine contractions. The patient later delivered a healthy baby via cesarean section at 38 weeks due to decreased fetal movement and breech presentation. This rare case of premature rupture of membranes in one of the twins before the viability term, followed by a successful delayed delivery, is presented here.